273 Fetal Loss in Severe Asthma and Posterior Healthy Pregnancy and Birth with the Use of Omalizumab—Case Report - Kuschnir, Fábio (World Allergy Organization Journal, 2012)
BACKGROUND: Pregnancy may aggravate asthma and result in life-threatening for both mother and foetus. The humanized monoclonal antibody omalizumab has proven to be effective in controlling severe asthma. The purpose of this case report is to present the effectiveness and safety of this medicine during pregnancy. METHODS: Case report of a severe asthmatic pregnant woman who had a previous foetal loss due to asthmatic exacerbation, and obtained a subsequent successful pregnancy and delivery with omalizumab use. RESULTS: KRF, 35, female, housewife, presented bronchial asthma associated with allergic rhinosinusitis since childhood with periods of remission and exacerbations. Since 15 years old, she presented progressive worsening of the disease with increased intensity and frequency of the attacks. In 2005 she became pregnant, progressing with severe attacks, emergency visits and hospital admissions, and requiring courses of systemic corticosteroids, despite continued treatment including combined of long-acting beta agonist (LABA) and inhaled corticosteroids (IC), besides Montelucast and Bamiphylline. Nevertheless, the pregnancy was interrupted at 8 months, due to the fetal death. Despite using regularly Formoterol (24 mcg/day) and Ciclesonide (640 mcg/day), the exacerbations became frequent, requiring continuous oral prednisolone, 20 mg daily, to achieve asthma control. Other risk factors for severe asthma were ruled out through extensive investigation. Omalizumab, 300 mg monthly, was introduced in July 2006, resulting in important improvement of the asthma control, allowing the discontinuation of systemic corticosteroids in 2 months, and subsequent reduction of Ciclesonide and formoterol doses. Discontinuation in Omalizumab use resulted in asthma worsening, despite the increment in the other medications doses. When omalizumab administration was restored, 8 months later, the asthma control was achieved again. In November 2010, she became pregnant and the same treatment plan for asthma was maintained. Only one episode of a mild exacerbation of asthma occurred due to a respiratory infection. The pregnancy reached full-term with a cesarean section in May 2011 with mother and newborn presenting satisfactory health conditions. CONCLUSIONS: Omalizumab has shown efficacy and safety in the control of severe asthma during pregnancy, reducing the risk of injury to health for both mother and newborn.